Innowacyjność regionalnej przestrzeni europejskiej w aspekcie rozwoju sektora usług - Markowska, Małgorzata; Strahl, Danuta (Innovativeness of European regional space in the aspect of service sector development, 2006)
The article presents research results regarding the innovativeness of European regional space at the NUTS-2 level. The thesis that innovative regions are characterized by the coincidence of high level of service sector development and high regional development, measured by GDP value per capita, as the basic measure of regional development, has been verified. The analysis of innovativeness was carried out based on the following stages: presentation of innovation denominator, presentation of regions innovativeness identification method, including the procedure of classification referring to analyzed objects, characterized by certain attributes, empirical studies identifying regions innovativeness regarding service sector development. Three variables were used for the identification of regions innovativeness: the share of employees in the sector of market services, the share of employees in the sector of non-market services and the level of GDP per capita in PPS (purchasing power standard). As the result of conducted classification three classes of European regions have been obtained which, in view of the agreed assumptions, may be regarded as innovative ones: the first class is made up of regions, in which values of each of the three variables are higher than the third quartile, so: the share of employed in the market service sector is higher than 39.2%, the share of employed in the non-market service sector is above 33.5% and the level of GDP per capita in PPS equals at least 23 840 PPS; the second class is comprised of regions, in which the variable value: the share of employed in market service sector and the value of GDP per capita is higher than the third quartile; the third class is made up of regions characterized by the variable value: the share of employed in non-market services and the value of GDP per capita higher than the third quartile. 43 regions, out of 250 analyzed, were qualified as the innovative ones, with regard to the development of services sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 215-225